The Effect Of Parliamentary Aspiration Communication on Student Enrolment Participation: The Mediating Role of Scholarship Awareness and The Moderating Role of Digital Literacy - Medya Apriliansyah (Prodi Ilmu Komunikasi Fakultas Komunikasi & Desain Kreatif, 2026)
This study examines the effect of parliamentary aspiration communication on student enrolment participation in higher education, with scholarship awareness as a mediating variable and digital literacy as a moderating variable, among grade XII students in Sukabumi Regency and Sukabumi City (West Java IV). A quantitative survey was conducted with 192 valid responses from SMA and SMK students, selected using cluster and purposive sampling. Data were collected using a Likert-scale questionnaire covering four constructs and analysed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS. The measurement model met reliability and validity criteria, with composite reliability values above 0.89 and AVE values above 0.62 for all constructs, and discriminant validity confirmed through Fornell–Larcker and HTMT tests. The structural model showed that parliamentary aspiration communication had a significant positive effect on scholarship awareness (β = 0.52; p < 0.001) and student enrolment participation (β = 0.24; p = 0.004), while scholarship awareness also had a significant positive effect on enrolment participation (β = 0.47; p < 0.001). Scholarship awareness was found to act as a complementary mediator in the relationship between parliamentary aspiration communication and student enrolment participation, with a significant indirect effect (β = 0.24; p < 0.001). In addition, digital literacy significantly moderated the relationship between parliamentary aspiration communication and scholarship awareness (β = 0.18; p = 0.011), indicating that the influence of parliamentary communication on awareness is stronger among students with higher digital literacy. These findings suggest that strengthening parliamentary communication on education, increasing students’ awareness of scholarships, and improving digital literacy are jointly important to enhance higher education enrolment among final-year secondary students in Sukabumi.